Why Only Us? On the Evolutionary Discontinuity of Human Language - Mendívil-Giró, José Luis (Analysis. Journal of Philosophical Research, 2020)
This article presents a characterization of human language and its evolution from a biolinguistic point of view. According to this point of view, language is a biological property of the human species (an instinct) and, therefore, the result of natural evolution. Despite this, it is argued that there is an evolutionary discontinuity between human language and the language of other species, although it is also argued that cognitive discontinuity does not imply biological discontinuity. The essential idea is that human language is special because it is not a communication system (which would have evolved from ancestral communication systems), but a thought system that, additionally, is used for social interaction (including communication). According to this approach, we can speculate that the evolution of specific aspects of human language was relatively sudden and recent in the history of our kind.